The periplasmic regulator ExoR inhibits ExoS/ChvI two‐component signalling in Sinorhizobium meliloti - Chen, Esther J.; Sabio, Erich A.; Long, Sharon R. (Molecular microbiology, 2008)
Summary Sinorhizobium meliloti requires ExoS/ChvI two‐component signalling to establish a nitrogen‐fixing symbiosis with legume hosts. The importance of ExoS/ChvI signalling in microbe–host interactions is underscored by the requirement of ExoS/ChvI orthologues for virulence of the related α‐proteobacteria Agrobacterium tumefaciens and Brucella abortus. In S. meliloti, ExoS/ChvI is a key regulator of gene expression for exopolysaccharide synthesis, biofilm formation, motility, nutrient utilization and free‐living viability. Previously, we showed that the novel conserved regulator ExoR interacts genetically with both ExoS and ChvI, and localizes to the periplasm of S. meliloti. Here, we show that ExoR physically associates with ExoS and that this association is important for regulating ExoS/ChvI signalling. We have identified point mutations in the Sel1‐like repeat region of ExoR that disrupt binding to ExoS and cause a dramatic increase in ExoS/ChvI‐dependent gene expression. Furthermore, we have found that physical interaction with ExoS stabilizes the ExoR protein. Together, our results indicate that ExoR binds to ExoS in the periplasm of S. meliloti to inhibit ExoS/ChvI activity, and that ExoR represents a novel periplasmic inhibitor of two‐component signalling.